2017
DOI: 10.1186/s40813-017-0057-2
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled field study to evaluate the efficacy and clinical safety of a single 8 mg/kg injectable dose of marbofloxacin compared with one or two doses of 7.5 mg/kg injectable enrofloxacin for the treatment of Actinobacillus pleuropneumoniae infections in growing-fattening pigs in Europe

Abstract: BackgroundAcute outbreaks of Actinobacillus pleuropneumoniae (APP) require rapid, effective, parenteral antimicrobial treatment. The efficacy and safety of a single, short-acting, high dose of marbofloxacin (Forcyl® swine 160 mg/mL) compared with 1 or 2 doses of 7.5 mg/kg enrofloxacin in APP outbreaks in European farms was studied.MethodsA controlled, randomised block, blinded, multicentre, field study was conducted on four farms with acute respiratory disease associated with APP. Animals with clinical signs o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 20 publications
2
13
0
Order By: Relevance
“…Acute clinical pleuropneumonia can be successfully treated by a single injection of fluoroquinolones in a dosage allowing concentration‐dependent bacterial killing, if App strains are susceptible (Grandemange et al., ). In an infection experiment, the high effectiveness of enrofloxacin against App compared to a tetracycline and procaine–penicillin was shown (Sjölund, Fossum, et al., ).…”
Section: Prevention Control and Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute clinical pleuropneumonia can be successfully treated by a single injection of fluoroquinolones in a dosage allowing concentration‐dependent bacterial killing, if App strains are susceptible (Grandemange et al., ). In an infection experiment, the high effectiveness of enrofloxacin against App compared to a tetracycline and procaine–penicillin was shown (Sjölund, Fossum, et al., ).…”
Section: Prevention Control and Treatmentmentioning
confidence: 99%
“…bial agents: ampicillin (sensitive <0.5, resistant >2.0), ceftiofur (sensi-tive <2, resistant >8.0), tulathromycin (sensitive <64), tilmicosin (sensitive <16, resistant >32), tildipirosin (sensitive <16), florfenicol (sensitive <2, resistant >8.0), tiamulin (sensitive <16, resistant >32), tetracycline (sensitive <0.5, resistant >2) (CLSI, 2015).Acute clinical pleuropneumonia can be successfully treated by a single injection of fluoroquinolones in a dosage allowing concentration-dependent bacterial killing, if App strains are susceptible(Grandemange et al, 2017). In an infection experiment, the high effectiveness of enrofloxacin against App compared to a tetracycline and procaine-penicillin was shown (Sj€ olund,Fossum, et al, 2011).…”
mentioning
confidence: 99%
“…However, it is reported that MR, as a single-dose of 10 mg/kg, could be effective in order to limit the risk of development of resistance, as multiple dosing of 2 mg/kg could achieve mutant prevention concentration (MPC) only for a short time after every dose (Vallé et al 2012 ). Based on this, we used MR as a single high dose as recommended for calves and pigs in previous studies (Grandemange et al 2012 , 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The calculated PK/PD indices were AUC/ MIC90 for selected time intervals (0-24 h, 24-48 h, 48-72 h) divided by 24 h, as suggested by for long acting formulations, and Cmax/MIC90. These indices were calculated using MIC90 values for the most common pathogens in swine (Grandemange et al, 2017).…”
Section: Methodsmentioning
confidence: 99%